Melanoma lentiginoso acral - León, Kennya Tamara (2016)
Acral lentiginous melanoma, located in the hands and feet, is the most frequent neoplasm in non-Caucasian races and usually occurs in support areas. We review the case of a 68-year-old woman who presents with a stain on the back of the fourth toe and is asymptomatic; was diagnosed melanoma by histopathology.